Mutual Projection in the Performance and the Criticism of Work in the Social Sciences: Reply to Obert - Mitroff, Ian I. (Academy of Management Review, 1984)
This article presents the author's reaction to the response of researcher S.L. Obert to the author's article “Archetypal Social Systems Analysis: On the Deeper Structure of Human Systems.” The way in which Obert initially read the author and the way in which he in turn reacted to him is evidence of one of the primary laws by which the psyche operates. One of Obert's most serious criticisms is that the author's paper exhibits a vision of a unidimensional, hierarchical model. The author's difficulties with Obert's response are summarized.